الترويض المعماري الذكي نحو بنية معمارية متكاملة (حالة الدراسة:البروزات في الأبنية السكنية في مدينة اللاذقية) - بدر, رنا (Latakia University Journal -Engineering Sciences Series, 2018)
تعتبر عملية التصميم المعماري عملية تكرارية يقوم بها المعماري مراراً وتكراراً للحصول على مفردة معمارية أو منتج معماري حائز على الرضا . تنطلق هذه العملية الترويضية وفق ثلاثة أطر لمن هذا التصميم ؟ وأين هذا التصميم؟ وكيف سيتم تنفيذه بمرور الزمن؟ وامكانية تطويره وتحسينه تلبية للمستجدات. وفي بحثنا هذا محاولة لتتبع العملية التكرارية بآلية ذكية يمكن من خلال (ضمان حالة التطوير الإيجابي للتصميم من خلال درجات كفاءته للاحتياجات البشرية، والسعي تدريجياً لزيادة هذه الدرجات بعملية ترويضية خاضعة لتدرّج ذكي ضامنة لدرجات كفاءة مرتفعة)، والتي يمكن الاحتذاء بها لطلاب العمارة إضافة للمعماريين المهنيين بغية التحسين والتطوير لتلبية الاحتياجات بشكل وافر. The architectural design process is a repetitive process that the architect repeatedly undertakes to obtain a satisfactory architectural vocabulary or architectural product. This taming process starts according to three frameworks of this design? Where is this design? How will it be implemented over time? And the possibility of developing and improving it to meet the latest developments. In this research, we try to follow the process of repetition with a smart mechanism that can (by ensuring the status of the positive development of the design through the degrees of efficiency of human needs, and gradually seek to increase these grades in the process of taming subject to intelligent gradation guaranteeing high degrees of efficiency), which can be followed for the students of architecture in addition to professional architects In order to improve and develop to meet the needs in abundance